Bisifusarium tonghuanum (Nectriaceae), a novel species of Fusarium-like fungi from two desert oasis plants - Sun, Bind-Da; Zhou, Yu-Guang; Chen, Amanda-Juan (Phytotaxa, 2017)
A Fusarium-like fungus was discovered when isolating fungi from surface sterilized plant samples collected in desert oasis of China. This fungus produced orange colonies on PDA medium and small, curved and 0-1 septum macro-conidia. Phylogenetic analysis based on tef1, β-tub, ITS and LSU rDNA sequences showed its belonging to a newly erected genus, Bisifusarium, thus the name Bisifusarium tonghuanum was introduced. Relationships of the new species with known taxa were discussed.